Reconceptualising the Cognition–Achievement Relationship in Secondary Mathematics: Evidence from a Classroom-Based Correlational Study - Ananda Safitri; Attin Warmi; Hanifah Hanifah (Program Studi Pendidikan Matematika, Universitas Majalengka, 2026)
This study aimed to examine the strength and direction of the relationship between mathematical thinking processes and mathematics learning outcomes among ninth-grade junior high school students. The research employed a quantitative nonexperimental correlational design to identify associative patterns between variables without inferring causal relationships. The population consisted of 476 students across twelve classes, and the sample was selected using purposive sampling, resulting in one intact class comprising 36 students. Data on mathematical thinking processes were collected through four constructed-response (essay) items designed to measure reasoning, conceptual linkage, and structured problem-solving abilities. Mathematics learning outcomes were obtained from students’ midterm examination scores as indicators of curriculum-based academic achievement. Data analysis was conducted in several stages, including descriptive statistical analysis and normality testing using the Shapiro–Wilk test. Due to non-normal distribution in one variable, the relationship between variables was analysed using Spearman’s rank correlation coefficient as a non-parametric alternative. The results indicated that students demonstrated relatively adequate levels of mathematical thinking; however, the correlation between mathematical thinking processes and learning outcomes was positive but weak and statistically non-significant (ρ = 0.211, p > 0.05). These findings suggest that mathematical thinking, while conceptually important, may not function as a strong standalone predictor of examination-based academic performance. The study implies that mathematics learning outcomes are influenced by multiple interacting cognitive and contextual factors, highlighting the importance of aligning assessment practices with higher-order thinking competencies to enhance the measurable contribution of mathematical reasoning to student achievement.